Knowledge management (KM) framework for the Malaysian construction consultant companies - Md. Rasli, Amran; Abd. Majid, Muhd. Zaimi; Baba, Maizan; Mohamed, Miswan @ Abdul Hakim (Faculty of Management and Human Resource Development, 2006)
This study is aimed to develop a framework that integrates knowledge management (KM) and information technology infrastructure (ITI) capabilities for the Malaysian construction consulting companies. A systematic two-step approach using the Delphi technique followed by a survey questionnaire was able to solicit responses by 19 experts and 122 consultants respectively. A rigorous statistical approach to ascertain data validity and reliability is conducted using factor analysis and Cronbach’s alpha respectively. Subsequently, independent sample t-tests were performed to demarcate KM attributes into either ‘exploitive’ or ‘explorative’, as well as ITI capabilities into either ‘exclusive’ or ‘standardised’. Through the integration of the findings, a four-quadrant matrix (‘exploitive’ or ‘explorative’ KM versus ‘exclusive’ or ‘standardised’ ITI capabilities) is finally proposed in this study.